Characterization of a Broadly Neutralizing Monoclonal Antibody against SARS-CoV-2 Variants - Tasnim Saifudin Zakir; Tao Meng; Lee Ching Pei Carmen; Justin Jang Hann Chu; Raymond Tzer Pin Lin; Mookkan Prabakaran (Viruses, 2022)
The constant mutation of SARS-CoV-2 has led to the emergence of new variants, which call for urgent effective therapeutic interventions. The trimeric spike (S) protein of SARS-CoV-2 is highly immunogenic with the receptor-binding domain (RBD) that binds first to the cellular receptor angiotensin-converting enzyme 2 (ACE2) and is therefore the target of many neutralizing antibodies. In this study, we characterized a broadly neutralizing monoclonal antibody (mAb) 9G8, which shows potent neutralization against the authentic SARS-CoV-2 wild-type (WT), Alpha (B.1.1.7), and Delta (1.617.2) viruses. Furthermore, mAb 9G8 also displayed a prominent neutralizing efficacy in the SARS-CoV-2 surrogate virus neutralization test (sVNT) against the Epsilon (B.1.429/7), Kappa (B.1.617.1), Gamma (P.1), Beta (B.1.351), and Delta Plus (1.617.2.1) RBD variants in addition to the variants mentioned above. Based on our in vitro escape mutant studies, we proved that the mutations V483F and Y489H within the RBD were involved in ACE2 binding and caused the neutralizing evasion of the virus from mAb 9G8. The development of such a cross-reactive neutralizing antibody against majority of the SARS-CoV-2 variants provides an important insight into pursuing future therapeutic agents for the prevention and treatment of COVID-19.